Tectonic archaeology : subduction zone geology in Japan and its archaeological implications - Barnes, Gina Lee, (Access archaeology., 2022)
The effects of tectonic processes on archaeological sites are evidenced by earthquake damage, volcanic eruptions, and tsunami destruction, but these processes also affect a broader sphere of landform structures, environment, and climate. An overview of tectonic archaeology is followed by a detailed summary of geoarchaeological fieldwork in Japan.